2018
DOI: 10.3892/ol.2018.7755
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and functional implications of the inhibitor of apoptosis proteins survivin and XIAP in esophageal cancer

Abstract: Abstract. Based on their overexpression and important roles in progression and therapy-resistance in malignant diseases, the inhibitor of apoptosis protein family (IAP) members, survivin and X-linked inhibitor of apoptosis protein (XIAP), represent attractive candidates for targeted therapy. The present study investigated the prognostic and biological relevance of survivin and XIAP in esophageal squamous-cell carcinoma (ESCC) and esophageal adenocarcinoma (EAC). Survivin and XIAP expression was analyzed by imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…Other studies previously reported a survival benefit for patients with lower expression of XIAP in comparison with patients expressing high levels of XIAP in esophageal squamous cell carcinoma (ESCC) but were not able to reveal a difference in OS in esophageal adenocarcinoma [23]. In contrast to the current study, only a relatively small group of patients was examined in which, due to the limited number of patients, sufficient subgroup analyses may not lead to significant results.…”
Section: Discussionmentioning
confidence: 63%
“…Other studies previously reported a survival benefit for patients with lower expression of XIAP in comparison with patients expressing high levels of XIAP in esophageal squamous cell carcinoma (ESCC) but were not able to reveal a difference in OS in esophageal adenocarcinoma [23]. In contrast to the current study, only a relatively small group of patients was examined in which, due to the limited number of patients, sufficient subgroup analyses may not lead to significant results.…”
Section: Discussionmentioning
confidence: 63%
“…All studies were retrospective design and the sample size ranged from 29 to 1103. The patients were diagnosed with various solid carcinomas, among which digestive tumors accounted for the most type, particularly gastric cancer (n=4) 25-28, colorectal cancer (n=3) 29-31, HCC (n=5) 12, 17, 32-34, esophageal cancer (n=2) 11, 35, cholangiocarcinoma (n=2) 36, 37 and pancreatic cancer (n=1) 38. And the remaining studies included breast cancer (n=4) 16, 18, 19, 39, NSCLC (n=2) 13, 40, head and neck cancer (HNC) (n=4) 41-44, thyroid cancer (n=4) 15, 45-47, prostate cancer (n=2) 14, 48, renal cancer (n=2) 49, 50 and other tumor types (n=5) listing as: sebaceous gland carcinoma, glioblastomas, ovarian cancer, bladder cancer and malignant mesothelioma 51-55.…”
Section: Resultsmentioning
confidence: 99%
“…It was slowly emerging as a potential therapeutic target for cancer management. Recently, many scholars have carried out series of studies to explore the expression of XIAP and its association with patient outcomes in different types of tumors, such as hepatocellular carcinoma (HCC), breast cancer, non-small cell lung cancer (NSCLC), esophageal cancer, thyroid cancer, prostate cancer 11-16. However, these results remain controversial.…”
Section: Introductionmentioning
confidence: 99%
“…The rest studies were further evaluated in full text and 31 were excluded due to unrelated, lacking enough data or other reasons. Eventually, 12 studies [ 12 , 14 22 , 24 , 25 ] met the inclusion criteria and were included. The study selection process was shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Dizdar et al [ 25 ] showed that XIAP could be a prognostic marker in ESCC but not in EAC. Their findings were consistent with our subgroup analyses results.…”
Section: Discussionmentioning
confidence: 99%